Pendampingan dan Pelatihan UMKM di Desa Kalijati oleh Kelompok KKN Universitas Singaperbangsa Karawang - Sembiring, Dian Agnesa; Azis, Muhamad Luthfi; Lathifah, Ayu; Khoirunissa, Okta; Fauzi, ⁠Ade Fathin; Ockta, Nina; Arienza, Bahrul Muhitz; Hidayah, Dahnia Putri; Maulana, Al Ikhsan (Penerbit Goodwood, 2024)
Purpose: Micro, Small, and Medium-sized Enterprises (MSMEs), as part of the national economy, also face challenges in improving their business capabilities, such as a lack of capital, management and operating skills, and marketing. Therefore, it is important to empower and assist MSMEs in improving their potential. One MSME mentoring activity can be implemented through the KKN program as a means of student community service. Kalijati Village, one of Unsika's KKN locations in 2024, has many people who conduct entrepreneurial activities. However, MSME owners' understanding of changing trends in the digital era, especially in online marketing strategies, is still minimal, as is their lack of attention to product packaging design. Methodology: This research was a qualitative study with a descriptive approach. This study was conducted in Kalijati Village, Kecamatan Jatisari, and Kabupaten Karawang. Results: This community service activity was carried out from January 15 to 29, 2024, for MSME owners in Kalijati Village. The series of community service activities carried out are: HPP the Cost of Goods Sold (HPP) calculation seminar, entrepreneurship seminar, and MSME assistance in product packaging and online marketing. Limitations: The limited data used in this study made the results suboptimal. Contribution: Assisting Kalijati Village MSMEs in improving their understanding of the calculation of cost of goods old (COGS) as well as assisting MSMEs in product packaging and online marketing.